Fiscal sustainability and low interest rates: what an indicator can('t) tell - Martin Werding (Empirica, 2021)
The indicator that is commonly used to assess the long-term fiscal sustainability of public finances in EU member states ("S2") is also defined if government borrowing rates are assumed to be permanently lower than the growth rate of GDP. Under these circumstances, however, it no longer provides a reliable orientation for fiscal policy. I illustrate these findings based on simulations prepared for the Fifth Sustainability Report published by the German Federal Ministry of Finance. In addition, I discuss the interpretation of the indicator in a low-interest environment and the assumption that relevant interest rates may continue to be low if there are substantial challenges for fiscal sustainability, e.g., through demographic ageing.
Keywords: H6; J11; E43; 330; Public budget; Public debt; Fiscal sustainability; Interest rates